Collecting data on organizational structures of trauma centers: the CAFE web service. Issue 1 (29th July 2020) - Brochhausen, Mathias; Ball, Jane W; Sanddal, Nels D; Dodd, Jimm; Braun, Naomi; Bost, Sarah; Utecht, Joseph; Winchell, Robert J; Sexton, Kevin W
Abstract : Background: During the past several decades, the American College of Surgeons has led efforts to standardize trauma care through their trauma center verification process and Trauma Quality Improvement Program. Despite these endeavors, great variability remains among trauma centers functioning at the same level. Little research has been conducted on the correlation between trauma center organizational structure and patient outcomes. We are attempting to close this knowledge gap with the Comparative Assessment Framework for Environments of Trauma Care (CAFE) project. Methods: Our first action was to establish a shared terminology that we then used to build the Ontology of Organizational Structures of Trauma centers and Trauma systems (OOSTT). OOSTT underpins the web-based CAFE questionnaire that collects detailed information on the particular organizational attributes of trauma centers and trauma systems. This tool allows users to compare their organizations to an aggregate of other organizations of the same type, while collecting their data. Results: In collaboration with the American College of Surgeons Committee on Trauma, we tested the system by entering data from three trauma centers and four trauma systems. We also tested retrieval of answers to competency questions. Discussion: The data we gather will be made available to public health and implementation science researchers using visualizations. In the next phase of our project, we plan to link the gathered data about trauma center attributes to clinical outcomes.